Bromatological quality of kikuyu grass in response to inoculation with mycorrhizal fungi and chemical fertilization - Ortiz A., Alejandro (2021)
Kikuyu (Cenchrus clandestinus) is the predominant grass in the Colombian high tropics and is the main forage in specialized dairy systems; however, it must be subjected to high doses of nitrogen (N) and phosphorus (P) from chemical sources. The aim of this study was to evaluate the effect of the arbuscular mycorrhizal fungi - FMA (Rhizophagus intraradices and Rhizophagus manihotis) under three levels of fertilization with N (0 [0%], 200 [50%] and 400 kg N ha-1 year-1 [100%]) and P (0 [0%], 100 [50%] and 200 kg P ha-1 year-1 [100%]) in dry matter content (DM%), crude protein (PC%), gross energy (EB), calcium (Ca%) and P (P%) in kikuyo. This study was carried out with the plants sown in pots and under mesh house conditions. The results indicate that the use of HFMA in the fertilization program improved some bromatological variables of the kikuyo grass, like what was found with the application of 400 kg N ha-1 year-1 and 100 kg P ha-1 year-1 which had positive effect on the protein concentration and grass energy. The FMA did not affect (p>0.05) the quality of the forage; however, R. intraradices showed to be more efficient in the uptake of N and P from the soil.